The Influence of Principal’s Participatory Leadership and School’s Culture on Distance Learning in the Covid-19 Period - Marliana, Lia; Ahyani, Nur; Indrawati, Sri Wahyu (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine whether there is an influence of the principal's participatory leadership and school’s culture on the implementation of distance learning at State Vocational School 1 of Prabumulih. The population of this study were 100 teachers at State Vocational School 1 of Prabumulih and the sample taken using the Slovin formula was 80 teachers. This type of research uses quantitative research with correlation and descriptive methods, while the sampling is done by random sampling, the research instrument uses a questionnaire. The results indicate that there is a significant influence between the principal's participatory leadership and school’s culture in the implementation of distance learning at State Vocational School 1 of Prabumulih. Then between the participatory leadership of the principal and school’s culture in the implementation of distance learning are accepted, which means that there is a simultaneous significant Influence between the participatory leadership of the principal and the culture schools in the implementation of distance learning at State Vocational School 1 of Prabumulih.